The Role of the Two-Wheel Patrol of the Sabhara Unit in the Prevention of the Crime of Theft in the Makassar Police District - Anzhari Mattenete (Advances in Police Science Research Journal, 2022)
This research is motivated by the rise of theft crimes that occur in Makassar City. The impact of this rampant number of cases has caused the condition of community security and security to be disturbed and disturbing to the community. The Sabhara Unit as one of the organizations that carries out the function of the police to prevent crime in the community is required to always be on standby. Therefore, the authors are interested in conducting research with the aim of knowing how the role of the two-wheeled patrol unit of Sabhara in preventing the crime of theft that occurs in the Makassar Police Station area, what factors affect the two-wheeled patrol unit of Sabhara and what actions are taken by the patrol unit. sabhara in preventing the crime of theft. The research was conducted using a qualitative approach, descriptive analytical research method, and data collection techniques through interviews, observations and document studies. The results of the research were analyzed using the P.O.A.C Management theory and SWOT theory with the role concept, the two-wheeled patrol concept, the Sabhara concept, the theft concept and the crime prevention concept. The results of the study concluded that the implementation of the two-wheeled patrol by the Sabhara unit with all the efforts made could be said to be quite good but there were still some shortcomings in the implementation of the patrol, namely the lack of personnel strength of the Sabhara unit, inadequate facilities and infrastructure and the lack of public awareness of crime. robbery. Based on the results of the research, the author gives advice to the Makassar Police Sat Sabhara, namely that in carrying out its duties it should eliminate stubbornness and change it with behavior that is always a protector, in carrying out crime prevention always coordinate with government agencies, stake holders, and the community.